Bioactivity of Cinnamomum spp. (Lauraceae) essential oils against Tuta absoluta (Meyrick, 1971) (Lepidoptera: Gelechiidae) and selectivity for Macrolophus basicornis (Stal, 1860) (Hemiptera: Miridae) - Figueiredo, Karolina Gomes de (2021)
The tomato moth Tuta absoluta (Meyrick, 1971) (Lepidoptera: Gelechiidae) is one of the main pests that cause economic losses in solanaceous crops. The objective of this study was to evaluate the bioactivity of the essential oils of Cinnamomum camphora var. linalooliferum, Cinnamomum camphora and Cinnamomum cassia (Lauraceae) against T. absoluta, and the life cycle of the pest after exposure to these oils, using age-stage, two-sex life table, as well as the evaluation of the major compounds cinnamaldehyde and linalool, leaf consumption and the susceptibility of the population used in the experiments to insecticides. We also evaluated the toxicity of the essential oils to the predator Macrolophus basicornis (Stal, 1860) (Hemiptera: Miridae), which were treated with 1 μL of the LD50 of the oils for T. absoluta. The essential oils of C. camphora var. linalooliferum, C. camphora and C. cassia were solubilized in acetone at concentrations of 0.05; 0.10 and 0.07 mg.mL-1, respectively, which correspond to the LD50 for T. absoluta. The caterpillars of the control treatment received acetone only. T. absoluta caterpillars of the 2nd instar were treated with 1 μL of the solution applied on their back with a microsyringe. Then, they were kept on tomato leaves cv Santa Clara inside Petri dishes under controlled conditions. The design was completely randomized with 100 replicates, each replicate being a caterpillar. The experiment lasted 55 days, until the second-generation insects reached the second instar. The population of T. absoluta evaluated showed tolerance to the insecticides fenpropathrin, cartap hydrochloride and chlorpyrifos. The major compounds cinnamaldehyde and linalool presented mortalities of 83.3% and 86.7% of T. absoluta caterpillars, potentially responsible for the insecticidal activity of the oils. The treatments with essential oils reduced the duration of the larval, pupal and adult stages of T. absoluta, in addition to significantly reducing demographic parameters such as fecundity, oviposition and viability of eggs and survival of first instar caterpillars. Regarding the adults of the predator M. basicornis, essential oils caused about 50% mortality. The essential oils of C. camphora var. linalooliferum, C. camphora and C. cassia showed great potential for T. absoluta management programs because of their toxicity to this lepidopteran pest and intermediate effect of up to 50% mortality to the predator M. basicornis.